A New Species of Ultratenuipalpus (Acari: Tenuipalpidae) from Brazil and Re-Description of Ultratenuipalpus meekeri (De Leon), the Type Species of the Genus, with DNA Barcodes - Elizeu B. Castro; Jennifer J. Beard; Ronald Ochoa; Gary R. Bauchan; Gabriel Otero-Colina; Ashley P. G. Dowling; Antonio C. Lofego; Reinaldo J. F. Feres (Animals, 2023)
Species of the genus Ultratenuipalpus bear a broad subquadrate propodosoma with many large, flattened, lanceolate to ovate dorsal setae. They also bear some plesiomorphic character states, such as the presence of three pairs of ventral ps setae. Here, we describe Ultratenuipalpus parameekeri Castro, Ochoa & Feres sp. nov. based on adult females, males, and immatures, collected on ferns from Brazil. We also re-describe Ultratenuipalpus meekeri (De Leon), the type species of the genus, based on types and newly collected material from Mexico, and include additional novel data (e.g., dorsal and ventral ornamentation, leg chaetotaxy, and setal measurements) in a standardized form. We include highly detailed images obtained using LT-SEM, accompanied by DNA barcodes, for both species. The ontogenetic additions of leg chaetotaxy are presented and discussed.